2000
DOI: 10.1161/01.cir.101.5.498
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic, Renal, and Hormonal Effects of Adrenomedullin Infusion in Patients With Congestive Heart Failure

Abstract: Intravenous infusion of AM has beneficial hemodynamic and renal effects in patients with CHF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
179
2
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 243 publications
(197 citation statements)
references
References 22 publications
11
179
2
4
Order By: Relevance
“…15 Previous human experiments have produced varied results on the effects of intravenous infusion of AM on aldosterone release. [8][9][10][11][12] Our study showed that suppression of aldosterone release by AM in the control group was significant but quite limited (Figure 3). A hypotensive reaction due to AM infusion was observed over a wide dosage range, but the suppressive effect of AM on aldosterone release was time and dose dependent, suggesting that there may be relatively high thresholds for suppression.…”
Section: Effects Of Adrenomedullin In Primary Aldosteronismmentioning
confidence: 73%
See 4 more Smart Citations
“…15 Previous human experiments have produced varied results on the effects of intravenous infusion of AM on aldosterone release. [8][9][10][11][12] Our study showed that suppression of aldosterone release by AM in the control group was significant but quite limited (Figure 3). A hypotensive reaction due to AM infusion was observed over a wide dosage range, but the suppressive effect of AM on aldosterone release was time and dose dependent, suggesting that there may be relatively high thresholds for suppression.…”
Section: Effects Of Adrenomedullin In Primary Aldosteronismmentioning
confidence: 73%
“…AM administration stimulates renin release. [8][9][10][11][12] On the other hand, AM can partially, but not completely, suppress increases in aldosterone induced by angiotensin II in humans. 17 In PA patients, renin activity is extremely suppressed, suggesting that AM could mediate essential aldosterone suppression.…”
Section: Effects Of Adrenomedullin In Primary Aldosteronismmentioning
confidence: 99%
See 3 more Smart Citations